Apolipoprotein E e4 allele influences aggressive behaviour in Alzheimer's disease. Issue 9 (16th August 2004) - Craig, D; Hart, D J; McCool, K; McIlroy, S P; Passmore, A P
Abstract : The rising number of people with cognitive impairment is placing health care budgets under significant strain. Dementia related behavioural change is a major independent risk factor for admission to expensive institutional care, and aggressive symptoms in particular are poorly tolerated by carers and frequently precipitate the collapse of home coping strategies. Aggressive change may result from known genetic risk factors for Alzheimer's disease (AD) and therefore accompany conventional markers such as apolipoprotein E (ApoE). We tested this hypothesis in 400 moderately to severely affected AD patients who were phenotyped for the presence of aggressive or agitated behaviour during the month prior to interview using the Neuropsychiatric Inventory with Caregiver Distress. The proportion of subjects with aggression/agitation in the month prior to interview was 51.8%. A significantly higher frequency of the e4 allele was found in individuals recording aggression/agitation in the month prior to interview (χ 2 = 6.69, df = 2, p = 0.03). The additional risk for aggression/agitation conferred by e4 was also noted when e4 genotypes were compared against non-e4 genotypes (χ 2 = 5.45, df = 1, p = 0.02, OR = 1.60, confidence interval (CI) 1.06 to 2.43). These results indicate that advanced Alzheimer's disease patients are at greater risk of aggressive symptoms because of a genetic weakness in apolipoprotein E.